Metronidazole for mild chronic prostatitis - Palhares, Dario (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Ten cases of chronic prostatitis are described. The solely manifestation of the disease was pain in case of direct stimulation of the prostate. The treat-ment with a single oral dose of 2 g of metronidazole extinguisted the symptoms.